Dastūr al-kātib fī taʿyīn al-marātib. Volume 1 - Munshī, Shams, (Miras Maktoob, ISBN: 9789004365452., 2019)
From the time that the art of writing was invented, people have been sending letters. This is true of the Sumerians who wrote on clay tablets 5.000 years ago, as it is true today in the information age. But not every letter is the same: a letter to a lover, a friend, or a business relation, each requires a different tone. In the case of official correspondence, the need for a standard is even more pressing than in industry or trade. In the medieval Islamic world with its highly developed bureaucracies, there evolved a special type of textbook in the form of manuals for secretaries. These would include general information on the secreterial trade as well as collections of sample letters. This Persian manual by Shams Munshī was completed in 767/1366 and dedicated to Sultan Uways Jalāyirī of Tabriz (d. 776/1374). Wide in scope and well organized, it was superior to anything written before it. 2 vols; volume 1.